Kreativitas Guru Dalam Mengatasi Keterbatasan Prasarana Sarana Pembelajaran PJOK - Akhmad Syarif; Dewi Ratna Juwita; Yositta Wisman (FKIP Universitas Palangka Raya, 2023)
This study aimed to determine teachers' creativity level to overcome the limitations of infrastructure in the PJOK learning process in junior high schools in the Katingan Tengah District, Katingan Regency. This research is a quantitative descriptive study. The method used in this study is a survey method with data collection techniques using questionnaires as primary data, observation, and documentation as secondary data. The population of this study was all PJOK teachers in junior high schools throughout Katingan Tengah District Katingan Regency, totaling 23 teachers. Analysis of the data used is a descriptive analysis of the percentage. The results showed that the creativity of sports and health physical education teachers in responding to the limitations of physical education facilities and infrastructure in junior high schools throughout Katingan Tengah District, Katingan Regency as a whole was categorized as one teacher (4%) in the very high category, six teachers (26.09%) in the category high, ten teachers (43.48%) in the medium category, four teachers (17.39%) in the low category, and two teachers (8.70%) in the very low category. The conclusion is that the creation of physical education and health teachers in response to the limitations of physical education facilities and infrastructure in junior high schools throughout Sukoharjo District, Sukoharjo Regency is in the medium category (43.48%)